Vulvar granular cell tumor - Fatma Cavide Sonmez; Nadiye Koroglu; Beril Guler; Dilek Sema Arici (Wolters Kluwer Medknow Publications, 2016)
Granular cell tumors (GCTs) are rare and approximately half of the all lesions arise from head and neck, especially from the tongue. However, they are rarely seen in the vulva. They can occur in patients of any age, but peak age incidence is in the fourth to sixth decades. They generally occur as small, slow growing, and skin-colored nodule. GCTs are usually benign, but malignant cases were reported. Recurrence can be seen in benign tumors with clear margins, but rates increase with positive margins. The treatment is complete surgical excision. We report a case of benign GCT of the vulva. A 41-year-old patient presented with vulvar mass, and biopsy was consisted with GCT.